2015
DOI: 10.1093/mnras/stv219
|View full text |Cite
|
Sign up to set email alerts
|

Cosmology and astrophysics from relaxed galaxy clusters – I. Sample selection

Abstract: This is the first in a series of papers studying the astrophysics and cosmology of massive, dynamically relaxed galaxy clusters. Here we present a new, automated method for identifying relaxed clusters based on their morphologies in X-ray imaging data. While broadly similar to others in the literature, the morphological quantities that we measure are specifically designed to provide a fair basis for comparison across a range of data quality and cluster redshifts, to be robust against missing data due to point-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
216
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(245 citation statements)
references
References 103 publications
(117 reference statements)
28
216
1
Order By: Relevance
“…This appears to contradict the prediction from simulations that the merger rate is a strong function of redshift (see, e.g., but is consistent with other groups that have studied the evolution of cluster morphology (e.g., Mantz et al 2015;Nurgaliev et al 2017). For the most massive halos ( >  M M 10 14 ), found that the rate of major (…”
Section: The Evolution Of the Halo Merger Ratementioning
confidence: 63%
See 3 more Smart Citations
“…This appears to contradict the prediction from simulations that the merger rate is a strong function of redshift (see, e.g., but is consistent with other groups that have studied the evolution of cluster morphology (e.g., Mantz et al 2015;Nurgaliev et al 2017). For the most massive halos ( >  M M 10 14 ), found that the rate of major (…”
Section: The Evolution Of the Halo Merger Ratementioning
confidence: 63%
“…The X-ray morphology of a galaxy cluster is commonly used as a probe of the cluster's dynamical state (e.g., Mohr et al 1995;Schuecker et al 2001;Weißmann et al 2013;Mantz et al 2015). Nurgaliev et al (2017) demonstrated that the measured value of a phot , which we use in this work to quantify morphology, is significantly elevated during a major merger for ∼1-2 Gyr, based on hydrodynamic simulations of 26 major (M 1 /M 2 >0.5) cluster mergers.…”
Section: X-ray Morphologymentioning
confidence: 92%
See 2 more Smart Citations
“…The selection of the sample of massive, relaxed clusters employed here is detailed in the first paper in this series (Mantz et al 2015a; hereafter Paper I). Papers II, III and IV (Mantz et al 2014(Mantz et al , 2016Applegate et al 2016) employ Chandra data for this sample to respectively constrain cosmological parameters, through gas-mass fraction measurements; scaling relations and thermodynamics of the ICM; and the average bias of the X-ray mass determinations.…”
Section: Introductionmentioning
confidence: 99%